Natural Killer Cell Recognition of Melanoma: New Clues for a More Effective Immunotherapy - Tarazona, Raquel; Duran, Esther; Solana, Rafael (Frontiers in Immunology, 2016)
Natural killer cells participate in the early immune response against melanoma and also contribute to the development of an adequate adaptive immune response by their crosstalk with dendritic cells and cytokine secretion. Melanoma resistance to conventional therapies together with its high immunogenicity justifies the development of novel therapies aimed to stimulate effective immune responses against melanoma. However, melanoma cells frequently escape to CD8 T cell recognition by the down-regulation of major histocompatibility complex class I molecules. In this scenario, Natural killer cells emerge as potential candidates for melanoma immunotherapy due to their capacity to recognize and destroy melanoma cells expressing low levels of major histocompatibility complex class I molecules. In addition, the possibility to combine immune checkpoint blockade with other NK cell potentiating strategies (e.g. cytokine induction of activating receptors) has opened new perspectives in the potential use of adoptive NK cell-based immunotherapy in melanoma.